CSF neurofilament light concentration is increased in presymptomatic CHMP2B mutation carriers. (9th January 2018) - Rostgaard, Nina; Roos, Peter; Portelius, Erik; Blennow, Kaj; Zetterberg, Henrik; Simonsen, Anja H.; Nielsen, Jørgen E.
Abstract : Objective: A rare cause of familial frontotemporal dementia (FTD) is a mutation in the CHMP2B gene on chromosome 3 (FTD-3), described in a Danish family. Here we examine whether CSF biomarkers change in the preclinical phase of the disease. Methods: In this cross-sectional explorative study, we analyzed CSF samples from 16 mutation carriers and 14 noncarriers from the Danish FTD-3 family. CSF biomarkers included total tau (t-tau) and neurofilament light chain (NfL) as a marker for neurodegeneration, phosphorylated tau (p-tau) as a marker for tau pathology, β-amyloid (Aβ) 38, 40, and 42 (Aβ38, Aβ40, and Aβ42 ) to monitor Aβ metabolism, and YKL-40 as a marker of neuroinflammation. Aβ isoform concentrations were measured using a multiplexed immunoassay; t-tau, p-tau, NfL, and YKL-40 concentrations were measured using sandwich ELISAs. Results: CSF NfL concentration was significantly increased in mutation carriers vs noncarriers. Further, CSF NfL concentration was significantly higher in symptomatic mutation carriers compared to presymptomatic carriers, and also significantly higher in presymptomatic carriers compared to noncarriers. No differences in t-tau and p-tau and YKL-40 concentrations between controls and mutation carriers were observed. CSF concentrations of the Aβ peptides Aβ38 and Aβ40 but not Aβ42 were significantly lower in mutation carriers compared to noncarriers. Conclusions: Increased NfL levels in presymptomatic individuals and in symptomatic patients with FTD-3 indicate a continuous process of neurodegeneration from the presymptomatic to symptomatic state. Although not specific for FTD-3 pathology, our data suggest that CSF NfL could serve as a valuable biomarker to detect onset of neurodegeneration in FTD-3 mutation carriers.